Lifelong Learning: A Debate Regarding the Appropriateness of Adult Education Faculty's Participation in Teacher Preparation Programs - Donna D. Amstutz; Scipio A.J. Colin III; Fred Schied; Vanessa Sheared (Adult Education Research Conference, 2001)
The academic study of adult education remains in a precarious position in schools of education because adult education is often viewed as neither necessary nor integral to the colleges' main mission: usually the preparation of beginning teachers.